Construction of a core collection of eggplant (Solanum melongena L.) based on genome-wide SNP and SSR genotypes - Miyatake, Koji (Breed Sci, 2019)
A core collection of eggplant (Solanum melongena L.) was developed based on a dataset of genome-wide 831 SNP and 50 SSR genotypes analyzed in 893 accessions of eggplant genetic resources collected in the NARO Genebank using the Core Hunter II program. The 893 accessions were collected worldwide, mainly Asia. Genetic variation and population structure among the 893 eggplant accessions were characterized. The genetic diversity of the Asian accessions, especially the South Asian and Southeast Asian accessions, forming the center of diversity in eggplant, was higher than that of the other regions. The resulting core collection, World Eggplant Core (WEC) collection consisted of 100 accessions basically collected from the high genetic diversity countries. Based on the results of the cluster and STRUCTURE analyses with SNP genotypes, the WEC collection was divided into four clusters (S1–S4). Each cluster corresponds to a geographical group as below, S1; the European, American and African countries, S2; the East Asian countries, S3; the Southeast Asian countries, S4; the South Asian and Southeast Asian countries. The genotype and phenotype data of the WEC collection are available from the VegMarks database (https://vegmarks.nivot.affrc.go.jp/resource/), and seed samples are available from the NARO Genebank (https://www.gene.affrc.go.jp/databases-core_collections.php).